Cover Image, Volume 56, Number 11, November 2021. Issue 11 (18th October 2021) - Allen, Julian; Panitch, Howard
Abstract : Cover Caption: The cover image is based on the Original Article Bronchopulmonary dysplasia—A historical perspective by Julian Allen and Howard Panitch https://doi.org/10.1002/ppul.25341 .